A Cross-Country Comparison of the Corporate Social Responsibility Orientation Between Indonesia and Thailand: Do Gender and Culture Matter? - Putra, Kadek Dwi Cahaya; Wattanametha, Phussadee; Saputra, Upayana Wiguna Eka; Widiantara, I Made; Elfarosa, Ketut Vini; Rahmanu, I Wayan Eka Dian (APMBA (Asia Pacific Management and Business Application), 2024)
Despite the increased concerns about the significance of CSR for business, only a few empirical studies of CSR orientation are available. Understanding stakeholders’ CSR orientations are pivotal to devising appropriate CSR strategies. This study investigates perceptions of CSR Orientation among Indonesian and Thai consumers and examines economic, legal, ethical, and philanthropic dimensions. A questionnaire with an imperative scale to measure relative importance was administered to 300 business students in both countries. Findings revealed that economic responsibility ranked the highest for both groups, aligning with previous empirical studies. However, significant variations emerged regarding legal, ethical, and philanthropic priorities. Thai consumers emphasized ethical responsibility, while their Indonesian counterparts prioritized legal and philanthropic dimensions. These distinctions challenged the universality of CSR frameworks, establishing a new perspective on the substantial influence of cultural, regulatory, and societal factors. Further, the study punctuated the demand for companies to adjust CSR strategies adhering to distinct national contexts. To strengthen comprehension of CSR orientations, further study is advised to explore cross-cultural differences, the impact of developmental stages, and diverse sample demographics. These findings encompass significant implications for businesses operating in multiple cultural settings, emphasizing the imperative of adapting CSR practices to engage with local communities and consumers effectively.